2017
DOI: 10.19080/argh.2017.03.555607
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Noninvasive Serum Biomarkers of Liver Fibrosis in Infants with Biliary Atresia

Abstract: Background: Biliary Atresia (BA) is the most common cause of chronic cholestasis in infants It is a destructive inflammatory obliterative cholangiopathy that affects varying lengths of both intrahepatic and extrahepatic bile ducts. Even after a successful surgery, scarring of the liver can continue, resulting in cirrhosis and its complications. Aim:The aim of this study is to evaluate different serological markers derived from routine investigations in the prediction of liver fibrosis in infants with BA.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…In this regard, a study by Behairy et al [46] found that, regarding the performance of FIB-4, the cutoff point to detect early fibrosis (F1-F2) was > 0.019 with AUC 0.750, and to detect advanced fibro-sis (F3-F4), it was > 0.045 with AUC 0.853. These results agree with Elhenawy et al [41], who reported that the AUC of FIB-4 was 0.0098 with AUC 0.644, 61.9% sensitivity, and 61.9% specificity to discriminating advanced fibrosis. More evidence came from the study by Pokorska-Spiewak et al [47], where FIB-4 at a cutoff point of 0.18, with AUC 0.708, 85.7% sensitivity, and 93.7% negative predictive value (NPV), helped in detecting any stage of fibrosis; the cutoff point was 0.09 with AUC 0.586.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this regard, a study by Behairy et al [46] found that, regarding the performance of FIB-4, the cutoff point to detect early fibrosis (F1-F2) was > 0.019 with AUC 0.750, and to detect advanced fibro-sis (F3-F4), it was > 0.045 with AUC 0.853. These results agree with Elhenawy et al [41], who reported that the AUC of FIB-4 was 0.0098 with AUC 0.644, 61.9% sensitivity, and 61.9% specificity to discriminating advanced fibrosis. More evidence came from the study by Pokorska-Spiewak et al [47], where FIB-4 at a cutoff point of 0.18, with AUC 0.708, 85.7% sensitivity, and 93.7% negative predictive value (NPV), helped in detecting any stage of fibrosis; the cutoff point was 0.09 with AUC 0.586.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study, Hwang et al [35] noted that both the FIB-4 score and APRI positively correlated with progressing clinical categories and showed good to excellent performances for distinguishing between different clinical categories in the present study. Also, Elhenawy et al [41] stated that APRI and FIB-4 were significantly correlated with fibrosis in BA and were significantly higher in those with advanced fibrosis (Russo F4 and F5), and they stated that these non-invasive serological markers, which are derived from simple routine laboratory tests, may be of help in predicting advanced fibrosis and in longterm follow-up of infants with BA and minimize the need for repeated follow-up liver biopsies. However, previous reports indicate that the FIB-4 score is unreliable for predicting liver fibrosis in BA and other pediatric liver diseases [27,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation